JQuery for Designers: Beginner's Guide - Second Edition - MacLees, Natalie (Packt Publishing, Limited, 2014)
A step-by-step guide that spices up your web pages and designs them in the way you want using the most widely used JavaScript library, jQuery. The beginner-friendly and easy-to-understand approach of the book will help get to grips with jQuery in no time. If you know the fundamentals of HTML and CSS, and want to extend your knowledge by learning to use JavaScript, then this is just the book for you. jQuery makes JavaScript straightforward and approachable - you'll be surprised at how easy it can be to add animations and special effects to your beautifully designed pages.